TEACHING SCHOOL INFORMATICS IN THE CONTEXT OF DIGITALIZATION OF EDUCATION - Bidaibekov, Е.Ы; Bosova, Л.Л; Oshanova, Н.Т (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
The article deals with teaching school informatics in the context of digitalization of education. We will present a brief description of the stages already passed by general education schools in Russia and Kazakhstan on the path of digitalization of education, and note the features of the content of computer science training in each of them. The differences in the content of school education in our countries have become noticeable only in the last decade; this period will be considered in more detail. The content of the school course of computer science, combining fundamental and applied aspects, should be continuously developed, thereby ensuring compliance with the current level of development of the field of computer science and information technology.